Evaluation of methionine supplementation to diets containing cassava meal for swine - Gómez G., Guillermo G.; Santos, J.; Valdivieso Garcia, Mauricio A. (1984)
The effect of methionine supplementation to diets conatining high levels (~ 65%) of cassava meal (CM) were studied with gestating and lactating gilts as well as with growing-finishing pigs. In both experiments, methionine supplementation did not improve (P>.05) the results obtained with the unsupplemented diets. Handling of the feed during the gestation period could explain the differences found in relation to those previously reported; group-feeding appeared to be responsible for the poorer reproductive performance previously obtained with CM-based diets. Diets for growing-finishing pigs based on CM and soybean meal produced results similar to those of the control diet (yellow corn-soybean meal), irrespective of methionine supplementation. Further studies using least-cost diets formulated to include 30% CM for gestating and lactating gilts, 40% CM for baby pigs and 20 and 30% CM for growing- finishing pigs produced normal performance and required balancing, when necessary, with less than .06% methionine. The CM price used was equivalent to 80% of the current sorghum price. Combinations of CM with soybean meal or with soybean meal-cottonseed meal-fish meal resulted in well-balanced least-cost diets.